Crystallisation behaviour of HDPE in PA6/EPDM-g-MA/HDPE ternary blend with different phase morphology. (27th May 2016) - Dou, R.; Wang, W.; Zhou, Y.; Gong, L.; Yin, B.; Yang, M.-B.; Xie, B.-H.
Abstract : Morphology of polyamide/maleic anhydride grafted ethylene-propylene-diene monomer/high density polyethylene (PA6/EPDM-g-MA/HDPE) blend and crystallisation behaviour of HDPE in PA6/EPDM-g-MA/HDPE blend were studied by scanning electron microscopy, transmission electron microscope and differential scanning calorimetry (DSC). Morphology observation revealed that core–shell morphology with shell of EPDM-g-MA and core of HDPE was formed in PA6 matrix. DSC test indicated that unexpected result of HDPE double crystallisation peaks emerged for ternary blend system. Also the low temperature crystallisation peak of HDPE was confirmed to be induced as a result of hindered nucleation of HDPE in fine dispersed core–shell particles and the process of crystalline shrinkage of PA6 matrix during cooling process. Furthermore, the factors influencing the crystallisation behaviour of HDPE were systematically studied in this work. The content of EPDM-g-MA and the time of melt mixing significantly affected the crystallisation behaviour of HDPE while the crystallinity of PA6 had a little effect on the crystallisation behaviour of HDPE. The results demonstrated an intimate relationship between phase morphology and crystallisation behaviour of HDPE.